Shareholding system reform in China privatizing by groping for stones - Ma, Shuyun (Edward Elgar, 2010)
Since the 1980s, there has been a global wave of transfer of state assets to private hands. China is a relatively late participant of this worldwide trend, yet, in the last decade it has emerged as one of the largest privatizing countries. Shu-Yun Ma argues that China's privatization is not based on any grand blueprint; rather, it is privatization by "groping for stones to cross the river", a well-known metaphor often attributed to Deng Xiaoping, meaning that the reform simply proceeds on a trial-and-error basis without being guided by any theory